Analisis Potensi Usaha Pengembangan Pembibitan Sapi Peranakan Onggole (Studi Kasus di Kabupaten Karanganyar Provinsi Jawa Tengah, Indonesia) - Sahala, Josua (Fakultas Pertanian, Universitas Timor, 2024)
This study aims to analyze the development potential of beef cattle breeding in Karanganyar Regency including financial business feasibility, SWOT analysis and development strategies as well. Determination of the research location in Karanganyar Regency using the location quotient (LQ) method in order to obtain 3 sub-districts including Jenawi, Jatiyoso and Mojogedang Sub-districts. Purposive sampling was used to select 40 PO (Ongole Peranakan) cattle breeders as respondents. The survey method was used to collect primary data from respondents and secondary data from related agencies. The net present value (NPV), benefit cost ratio (BCR), internal rate of return (IRR), payback period of credit (PPC), and break event point criteria were used in the feasibility analysis of the cattle feedlot business (BEP). SWOT analysis was also used in the analysis of the PO cattle development strategy. The analysis revealed that the PO cattle breeding business is not financially feasible over an 8-year period with a discount factor of 12%/year, but it is feasible if labor is not valued in money. The SWOT analysis turned out the livestock rearing system, easy to obtain forage, financially feasible conditions, and livestock breeding methods are the internal strengthsInternal weaknesses include a lack of information on beef cattle farming, farmers' lack of knowledge, and farmers' weak bargaining position. External opportunities include the supply of business capital and the use of breeding technology. External threats include livestock diseases, competition for beef cattle from other areas, and uncontrolled livestock sales. PO cattle breeding business in Karanganyar Regency is feasible.